An Econometric Analysis of the Japanese Demand for Indonesian Tuna - Farradia, Yuary (1995)
The objective of this study was to evaluate the Japanese demand far Indonesian tuna Tuna which consisted of two species (Yellowfin and Bigeye) were observed in terms of fresh and frozen form at two price levels. Secondary data were collected from the institution as related to tuna information as well as references. In addition, interview with experts in tuna was also conducted. The data were then analysed using 2SLS method to construct a demand model. Tuna market in Indonesia is mostly controlled by four state owned companies. The marketing channel starts with fisherman and ends with the broker or exporters. However, some companies exported tuna directly or indirectly. The price of tuna export follows the international price in Japan, which is determined by a grading system based on 'torro' content and freshness. Statistical analysis using 2SLS shows a relationship among tuna species in terms of fresh and frozen forms at low and high price, respectively. The Japanese demand for fresh yellowfin in general, is determined by its previous demand, its own price and per capita income. However, at low price level, it is also determined by price of frozen yeUowfin and price of shrimp; whilst at high price level, fresh yellowfin is determined by price of fresh bigeye. The Japanese demand for fresh bigeye at low price level is determined by its previous demand, its own price, price of frozen bigeye, price of shrimp and per capita income which has negative sign. For high price level, fresh bigeye demand is determined by its previous demand, its own price, price of shrimp and per capita Income. The Japanese demand for frozen bigeye at low price is determined by its previous demand, its own price, price of frozen yellowfin and price of shrimp. However, for high price level, it is determined by its previous demand, price of shrimp and per capita income, which has negative sign. In terms of elasticity, price elasticity for the overall tuna species in this study is inelastic. Income elasticities are, however, elastic.